COMPARATIVE STUDY OF EFFICACY OF JATYADI GHRITA PICHU AND YASTHIMADHU GHRITA PICHU IN THE MANAGEMENT OF PARIKARTIKA (FISSURE- IN-ANO) - Mruthyumjaya Rao, *Meda; Kumar, P.Hemantha; Panda, Purnendu; Das, Bikartan (International Journal of Ayurveda and Pharma Research, 2016)
The condition Parikartika has been mentioned in the Ayurvedic literature as one of the fifteen kinds of disorders which may result from an injudicious use of purgatives owing to the ignorance of the physician or of the patient. The acute fissure is a superficial splitting of the anoderm characterized by severe pain, sometimes associated with bleeding per rectum during/after defaecation. Application of local anesthetics, anal dilatation, sphincterotomy, and fissurectomy (chronic fissure) are usually in practice. But these procedures have sometimes associated with some complications like post operative anal stenosis, sphincter incontinence etc. To overcome such problems and to provide cheap, simple, ambulatory and effective treatment, a combined therapy has been kept on trial on the basis of the treatment mentioned in the ancient literature in the management. Aim and objectives: Evaluation of clinical efficacy of Pichu application of Jatyadi Grihta and Yasthimadhu Grihta in the management of Fissure- in-ano (Parikartika). Materials & Methods: Taking this view in to consideration, a modified regimen with Jatyadi ghtrita and Yasthimadhu ghrita in Pichu form in two different groups along with Panchasakara churna have been kept on trial on 100 patients in each group in the Ano-Rectal Clinic of the Institute. Results and Conclusion: The results were assessed and compared and it was found that both the medicines were equally effective without any complications in the management of Fissure-in-ano.